Upaya Meningkatkan Pemahaman Nilai Moral Agama Melalui Metode Bercerita Pada Anak Usia 5-6 Tahun Di TK Pembina 02 Rumbio Jaya - Della Safitri; Yenda Puspita; Nurmalina Nurmalina (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This research is motivated by the low understanding of moral values ​​in group B children of Pembina 02 Rumbio Jaya Kindergarten, Simpang Petai Village, Rumbio Jaya District, Kampar Regency. The solution to this problem is by implementing the storytelling method. This study aims to determine whether the storytelling method can improve understanding in children at Pembina 02 Rumbio Jaya Kindergarten. The subjects in this study consisted of 15 children, 8 girls and 7 boys, the method used in this study was the Classroom Action Research (CAR) method. This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings, each meeting consisted of the following activities: Planning, Acting, Observing and Reflecting. Data collection techniques were carried out through observation and documentation, the results of the study showed that there was an increase in children's understanding of moral values ​​in each of the child's indicators, starting from the pre-action, most children were still in the